1997
DOI: 10.1111/j.1532-5415.1997.tb04509.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Antipsychotic Withdrawal or Dose Reduction in a Randomized Controlled Trial of Provider Education

Abstract: Focused provider education programs may facilitate antipsychotic reduction above and beyond that attributable to regulatory changes. Patients who are poor candidates for total antipsychotic withdrawal may tolerate substantial dose reductions, which should reduce their risk of adverse antipsychotic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 13 publications
2
47
0
2
Order By: Relevance
“…Changes in prescribing have been found for about 5% of patients of general medical practices that have received academic detailing, although some studies demonstrated changes in prescribing practices that affected as many as 50% of patients (14). When delivered with additional intensive training, academic detailing reduced use of antipsychotics among elderly nursing home residents (15). In contrast, a recent study found that four inperson educational visits did not reduce antipsychotic polypharmacy in a Danish municipality, but the meetings were poorly attended (16).…”
Section: Strategies To Improve Quality Of Prescribingmentioning
confidence: 99%
“…Changes in prescribing have been found for about 5% of patients of general medical practices that have received academic detailing, although some studies demonstrated changes in prescribing practices that affected as many as 50% of patients (14). When delivered with additional intensive training, academic detailing reduced use of antipsychotics among elderly nursing home residents (15). In contrast, a recent study found that four inperson educational visits did not reduce antipsychotic polypharmacy in a Danish municipality, but the meetings were poorly attended (16).…”
Section: Strategies To Improve Quality Of Prescribingmentioning
confidence: 99%
“…Informationsprogramme und Fortbildungen für Ärzte und/oder Personal wirkten sich positiv auf die psychopharmakologische Versorgungspraxis aus (Avorn & Monane, 1992;Meador et al, 1997;Snowdon, 1999;Roberts et al, 2001;Eide & Schjot, 2001).…”
Section: Fortbildung Von äRzten Und/oder Pflegepersonalunclassified
“…One nonrandomised study evaluating the effect of a neuroleptic education programme for physicians and nurses in nursing homes found a 72% decrease in neuroleptic use following the intervention, compared with a 13% decrease in the non-intervention nursing homes (Ray et al, 1992). Other similar, but randomised interventions have resulted in neuroleptic use reductions of 18% (Avorn et al, 1992), 23% (Meador et al, 1997) and 50% (Rovner et al, 1996). Hence educational interventions in themselves are quite effective in reducing neuroleptic usage in nursing homes, although it is likely that such effects are less enduring than those resulting from legislative reforms, such as OBRA.…”
Section: Voluntary Efforts and The Role Of Educationmentioning
confidence: 99%
“…A reasonable conclusion that can be drawn from the existing literature is that more research and controlled trials are needed to demonstrate both the efficacy and long-term safety of these drugs in their use to treat nursing home residents. Furthermore, even residents who may turn out to be poor candidates for a total withdrawal of neuroleptics are probably good candidates for at least a reduction in dose (Meador et al, 1997).…”
Section: Consequences Of Withdrawing Neurolepticsmentioning
confidence: 99%